Biomedical mementos: Ernst von Brücke, founder of Austrian physiology - Triarhou, Lazaros (Medicina Historica, 2024)
This vignette commemorates the pioneer Austrian physiologist Ernst Wilhelm von Brücke in conjunction with a special plaquette commissioned at the 8th triennial International Congress of Physiologists which was held in Vienna in 1910.